Obituary: Professor Alexander Kessenikh (1932-2021) - Andrey V. Andreev; Vadim A. Atsarkin; Konstantin V. Ivanov; Gennady E. Kurtik; Pierandrea Lo Nostro; Vasily V. V. Ptushenko; Konstantin A. Tomilin; Natalia V. Vdovichenko; Vladimir P. Vizgin (Substantia, 2022)
On September 15, 2021, professor Alexander V. Kessenikh died. He was known for his works on nuclear magnetic resonance (NMR) and history of science.